Multi-Criteria Selection and Screening for Karnal Bunt Resistance of Wheat (Triticumaestivum L. Em. Thell.) in Eastern Uttar Pradesh (Global Journal of Science Frontier Research, 2023)
Twenty wheat germplasm were evaluated on 14 parameters in an experiment at Center for Research and Development CRD Gaunar Usaraha Gorakhpur U P in a randomized block design with three replications The objective of the experiment was to select top five good performing genotypes on the basis of all the parameters and extent of Karnal bunt KB infestation Normalized cumulative ranks were used to assess the relative performance of twenty genotypes KOH seed soaking technique was used to assess the extent of Karnal bunt infestation Based on normalized accumulating ranks the performance order of twenty wheat genotypes isHD3117 HPYT480 HPAW152 HD3271 HPAN196 HPYT443 HPAN165 HD3226 HPYT409 HPAN153 HPYT474 CSW18 HPYT424 HPYT489 HPYT441 HPYT490 HPYT426 HPYT418 HPAN163 and HPYT446 Four genotypes were completely resistant Sixteen genotypes were susceptible to Karnal bunt and infestation ranged from 1 33 HPYT-418 to 30 HPYT-446 High performer genotypes like HD3117 HPYT480 HPAW152 HD3271 HPAN196 and Karnal bunt resistant genotypes like HPYT409 HPAN153 HPYT489 and HPYT 490 should be recommended for cultivation in this area
Keywords: ideotype; karnal bunt; normalized cumulative ranks; selection